Disoriented Law Enforcement Against Corporations Commit Money Laundering - R.B. Muhammad Zainal Abidin; Mahendra Suhartono; Idham Halik Nussy (Universitas Islam Malang, 2023)
Money laundering is an extraordinary crime that has a wide impact, not only threatening the stability of the economy and the integrity of the financial system, but also endangers the joints of community and state life. Money laundering can be committed by an entity called a corporation, this is evidenced by the recognition of the corporation in Act Number 8 of 2010. In law enforcement against corporations that commit money laundering, the corporation may be sentenced to an additional crime of dissolution of the corporation,but the criminal dissolution of the corporation has an impact on an innocent person such as workers or laborers who depend on their lives to the corporation, so it is disoriented between enforcing the law or not that commit money laundering. The purpose of this study is determine the law enforcement against corporations that commit laundering acts that are substantive justice, so that appropriate punishment can be known in law enforcement. This research is legal research, that is research that seeks the truth of coherence, using statute approach and conceptual approach. The results of this study concluded, in law enforcement against corporations that commit money laundering can be done 3 (three) approaches, first non-punitive punishment, second vicarious liability and identification theory approach and third restorative justice approach with due regard to the principle of efficiency and justice that reflects the values of objectivity, honesty, impartiality, and rationality.